Business process modeling languages: a comparative framework - Pereira, José Luís (2016)
Underlying any Business Process Management (BPM) project is the need to represent business processes, using an appropriate language. In this paper, based on a thorough review of the relevant literature, we made a comparative analysis of five business process modeling languages, widely used in the context of BPM projects. The main objective is to understand the strengths and major limitations of each one, in order to draw a comparative perspective between them. For this purpose, we have created a comparative framework in which each one of the languages are characterized regarding a number of relevant criteria. Finally, a prototype specifically developed to support this framework, is presented. The purpose of this prototype is to assist users in choosing a suitable business process modeling language, according to their specific needs.